Tolerance of skin care regimen in healthy, full-term neonates - Iarkowski LE; Tierney NK; Horowitz P (Dove Medical Press, 2013)
Laura Ellen Iarkowski,1 Neena K Tierney,1 Paul Horowitz21Johnson & Johnson Consumer Companies, Inc, Skillman, NJ, USA; 2Discovery Pediatrics, Valencia, CA, USAPurpose: To assess the tolerance of a baby cleanser and lotion (both lightly fragranced) on healthy, full-term neonates.Materials and methods: Twenty-six infant–mother pairs were enrolled in a 6-week, nonrandomized, controlled-use study that took place in the routine setting of a pediatric clinic and mothers’ homes. During study weeks 1 to 6, neonates were bathed by their mother with water and a test cleanser (JOHNSON'S® HEAD-TO-TOE® Baby Wash). During study weeks 1 to 3, mothers also applied test lotion (JOHNSON'S® Baby Lotion) to the babies’ skin immediately after bathing and one to three times/day on bathing and non-bathing days. During study weeks 4 to 6, no lotion was applied. At baseline and weeks 3 and 6, the infants’ pediatrician or mother or both performed visual skin assessments.Results: Twenty-three infant–mother pairs completed the study. The mean age of neonates at enrolment was 17.4 days (range, 13–28 days). Pediatrician observations found no clinical signs of irritation, erythema, or dryness with any significant difference in scores of these parameters compared with baseline throughout the study. Assessment of skin softness, smoothness, dryness, and overall skin condition was very good at baseline and remained so with minimal changes throughout the study. Mothers reported improvements versus baseline (P ≤ 0.05) in overall skin appearance, moisturization, softness, and smoothness on the arms and legs at weeks 3 and 6. A total of four (15.4%) subjects experienced adverse events. For three of the subjects, the investigator suspected that the adverse events were unrelated to either of the test products. In one participant, the cause of the adverse event could not be determined.Conclusion: The use of a lightly fragranced nonstinging baby cleanser, with or without a lightly fragranced baby lotion, was well tolerated by newborns and resulted in observable skin benefits per the pediatricians’ and mothers’ assessment.Keywords: bath, cleanser, fragrance, infant, lotion, neonate